Evaluation of the Effects of Extracts Containing Valeriana officinalis and Piper methysticum on the Activities of Cytochrome P450 3A and P-Glycoprotein - Nascimento, Mariana de Lima; do Nascimento, Sara Batista; Lima, Ednalva de Souza Pereira; de Oliveira, Flávio Martins; dos Santos, Rafael Rocha; Cesar, Isabela da Costa; de Castro, Whocely Victor (Planta Medica, 2024)
This work investigated interactions ascribed to the administration of phytomedicines containing Valeriana officinalis and Piper methysticum with conventional drugs. The phytomedicines were characterized by HPLC and administered per os to male Wistar rats, either concomitantly or not with the CYP3A substrate midazolam. To distinguish between the presystemic or systemic effect, midazolam was given orally and intravenously. The effects on the P-gp substrate fexofenadine uptake by Caco-2 cells were examined. The valerenic acid content was 1.6 ± 0.1 mg per tablet, whereas kavain was 13.7 ± 0.3 mg/capsule. Valerian and kava-kava extracts increased the maximum plasma concentration (Cmax) of midazolam 2- and 4-fold compared to the control, respectively. The area under the plasma concentrations versus time curve (AUC(0-∞)) was enhanced from 994.3 ± 152.3 ng.h/mL (control) to 3041 ± 398 ng.h/mL (valerian) and 4139 ± 373 ng.h/mL (kava-kava). The half-life of midazolam was not affected. These changes were attributed to the inhibition of midazolam metabolism by the enteric CYP3A since the i. v. pharmacokinetic of midazolam remained unchanged. The kava-kava extract augmented the uptake of fexofenadine by 3.5-fold compared to the control. Although Valeriana increased the uptake of fexofenadine, it was not statistically significant to that of the control (12.5 ± 3.7 ng/mg protein vs. 5.4 ± 0.3 ng/mg protein, respectively). Therefore, phytomedicines containing V. officinalis or P. methysticum inhibited the intestinal metabolism of midazolam in rats. Conversely, the P-gp-mediated transport of fexofenadine was preferably affected by kava-kava.
Keywords: Valeriana officinalis; Caprifoliaceae; Piper methysticum; Piperaceae; cytochrome P450; P-glycoprotein